Working with children in the early years - Cable, Carrie; Miller, Linda; Goodliff, Gill. (London ; New York : Routledge ; Milton Keynes : Open University, 2010)
Working with Children in the Early Years is an accessible introduction to early years theories, policy and practice, offering practitioners in a diverse range of settings the opportunity to develop their knowledge, understanding and skills for working with young children. This fully updated second edition builds on new government agendas and interests in supporting quality provision for young children and their families. Bringing together current research and thinking in a broad range of areas, it covers:the diversity of practitioner roles and multi-agency working working with families listeni.
Includes bibliographical references and index.
Keywords: Education, Preschool -- Great Britain; Preschool children -- Services for -- Great Britain; EDUCATION -- Preschool & Kindergarten